Population Dynamics of Aedes aegypti and Dengue as Influenced by Weather and Human Behavior in San Juan, Puerto Rico - Barrera, Roberto; Amador, Manuel; MacKay, Andrew J. (PLOS Neglected Tropical Diseases, 2011)
Author Summary Previous studies on the influence of weather on Aedes aegypti in Puerto Rico suggested that rainfall influenced mosquito populations and dengue incidence in the drier areas of the island. We studied temporal changes in Ae. aegypti in areas where rainfall is more uniformly distributed throughout the year. Changes in adult mosquitoes were monitored with BG-Sentinel traps and oviposition activity with CDC enhanced ovitraps. We also counted the number of mosquito pupae in containers with water during the drier and wetter parts of the year to determine the contribution of humans and rainfall to mosquito production. Mosquito dynamics was compared with dengue incidence in the municipalities investigated in the study (November 2007–December 2008). We found that the population of Ae. aegypti was driven by weather and human activities, and peaks in mosquito density preceded maximum dengue incidence during the rainy season. Even though Puerto Rico has a reliable supply of tap water and an active tire recycling program, water storage containers (e.g., 5-gal pails, drums) and discarded tires were important mosquito producers. We also documented for the first time that water meters are important producers of Ae. aegypti. This longitudinal study contributes to a better understanding of the complex dynamics of weather, human behavior, mosquito vectors, and dengue virus transmission in an endemic country.